A case of HIV, leprosy co-infection - presenting as immune reconstitution inflammatory syndrome - Romita Bachaspatimayum (Our Dermatology Online, 2018)
Though leprosy was officially declared eliminated in India, new cases continue to be reported. Introduction of Highly Active Antiretroviral Therapy (HAART) for Human Immunodeficiency Virus (HIV) infection in 1996, caused emergence of a new condition called Immune Reconstitution Inflammatory Syndrome (IRIS), which is the paradoxical deterioration of clinical status following HAART initiation. A 49 years old male patient who came with the complaints of dry skin and numbness of limbs 3 weeks after starting HAART was found to have IRIS syndrome and started on (MB- MDT) after which he developed type 1 lepra reaction. He was managed with systemic steroids with prompt recovery. Case is being reported to create awareness of this condition as more and more number of patients may be put on HAART due to increasing HIV prevalence in the region which may in turn lead to increase incidence of IRIS.